Avascular necrosis of the femoral head masquerading as back pain - Mohsin, Ibrahim; Ahmed, Habeeb M (Indian Journal of Case Reports, 2018)
Avascular necrosis causes severe joint destruction requiring a major surgical procedure for treatment. It is more prevalent in the elderly population and is initially asymptomatic. Here, we report the case of an 85-year-old woman who was scheduled for surgical intervention for severe back pain. On further evaluation, she was diagnosed with avascular necrosis of hip with pain radiating to her back. Nonclassical clinical presentation, nonambulatory status of the patient, and multiple pain locations masking the primary site such as in this case are some of the factors that make avascular necrosis a formidable diagnostic challenge.